Miscellaneous New species of Brazilian Bromeliaceae - Leme, Elton M.c.; Kollmann, Ludovic J.c. (Phytotaxa, 2013)
We describe and illustrate 14 miscellaneous new Bromeliaceae species from the Brazilian states of Bahia, Espírito Santo, Minas Gerais, Rio de Janeiro and São Paulo: Aechmea ituberaensis, A. pendulispica, Alcantarea acuminatifolia, A. occulta, Cryptanthus aracruzensis, C. ilhanus, C. rigidifolius, C. tabuleiricola, C. viridipetalus, Neoregelia desenganensis, N. insulana, N. watersiana, Vriesea saltensis, and V. sanctaparecidae. The morphological affinities of the new taxa are also discussed.